ØªØ¹ÙÙÙ Ø§ÙÙØºÙØ© Ø§ÙØ¹Ø±Ø¨ÙÙØ© Ø¨Ø¬Ø§Ù Ø¹ÙØ© Ø¥Ù ÙØ§Ù Ø¨ÙØ¬ÙÙÙ Ø§ÙØ¥Ø³ÙÙØ§Ù ÙÙØ© Ø§ÙØÙÙÙ ÙÙØ© Ø¨ÙØ§Ø¯ÙÙØ¬ Ø¨ÙÙÙ Ø£/Ø¯ Ù Ø³ÙØ§Ù Ø²Ø¬ÙÙÙ Ø±Ø¦ÙØ³ Ù Ø±ÙØ² Ø§ÙÙØºØ© Ø¨Ø¬Ø§Ù Ø¹Ø© Ø¥Ù Ø§Ù Ø¨ÙØ¬ÙÙ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙØ? - Zajuli, Masnal (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
The significance position of teaching and learning process of Arabic in State Institute for Islamic Studies âImam Bonjolâ of Padang is in line with the original existence of this institution; that is to produce credible Muslim scholars who are committed to uphold the right and eliminate the sinful.Â It is expected that through the teaching and learning process of Arabic, will enable the students to explore the teaching of Islam from the original sources written in Arabic, to use the language for communication, as well as to teach it to other people.Â Problems encountered by the institution have been continually resolved through some trainings provided for the instructors. Technical training and assistance from Sudan, Saudi Arabia, and Marocco are currently incorporated in conjunction with Arabic teaching.